2010
DOI: 10.1021/jo100076g
|View full text |Cite
|
Sign up to set email alerts
|

Mutremdamide A and Koshikamides C−H, Peptide Inhibitors of HIV-1 Entry from Different Theonella Species

Abstract: A new sulfated cyclic depsipeptide, termed mutremdamide A, and six new highly N-methylated peptides, termed koshikamides C–H, were isolated from different deep-water specimens of Theonella swinhoei and Theonella cupola. Their structures were determined using extensive 2D NMR, ESI, or CDESI and QTOF-MS/MS experiments and absolute configurations established by quantum mechanical calculations, advanced Marfey's method, and chiral HPLC. Mutremdamide A displays a rare 2-amino-3-(2-hydroxyphenyl)propanoic acid and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 37 publications
0
53
0
2
Order By: Relevance
“…From deep-water specimen of T. swinhoei and Theonella cupola sulfated cyclic depsipeptide, termed mutremdamide A, and six highly N-methylated peptides, termed koshikamides C-H, were isolated and the structure of unusual AAs was determined using advanced Marfey's method and chiral HPLC together with intensive use of NMR and mass spectrometric methods [84].…”
Section: Marine Spongesmentioning
confidence: 99%
“…From deep-water specimen of T. swinhoei and Theonella cupola sulfated cyclic depsipeptide, termed mutremdamide A, and six highly N-methylated peptides, termed koshikamides C-H, were isolated and the structure of unusual AAs was determined using advanced Marfey's method and chiral HPLC together with intensive use of NMR and mass spectrometric methods [84].…”
Section: Marine Spongesmentioning
confidence: 99%
“…3). The total absolute deviation (TAD) [12,13] between the experimental and calculated values (Table 2, Fig. 3) suggested that the calculated SSCCs of diastereomer I in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The SSCC of each rotamer was calculated using the same theory and basis set in Gaussian09 [11]. The total absolute deviation (TAD) [12,13] between experimental and calculated values was used to suggest the most relevant conformers, and by extension of the empirical results, their configuration.…”
Section: Methodsmentioning
confidence: 99%
“…Celebeside A neutralized HIV-1 in a single-round infectivity assay with an IC50 value of 1.9±0.4μg/mL while the nonphosphorylated analog celebeside C was inactive at concentrations as high as 50 μg/mL 69 . HIV cyclodepsipeptide, homophymine A, was isolated from a New Caledonian collection of the marine sponge Homophymia sp.…”
Section: Anti-hiv Peptidesmentioning
confidence: 99%
“…Koshikamides F and G differ from B and H in part by the presence of the conjugated unit 2-(3-amino-5-oxopyrrolidin-2-ylidene)propanoic acid. Cyclic koshikamides F and H inhibited HIV-1 entry at low micromolar concentrations while their linear counterparts were inactive 69 . The origin and role of bioactive peptides inside the sponges in many cases is unclear.Several of these substances possess a great potential for drug development, but none has given origin to a commercial medication so far.…”
Section: Anti-hiv Peptidesmentioning
confidence: 99%